Let f(x) = 2x^3 + x^2 - 5x + c. Given that f(1) = 0 find the values of c.

In order to solve this question we simply must substitute x=1 into f(x).

If we carry out this substitution we see that

f(1) = 2(1^3) + (1^3) -5(1) + c = 2(1) + (1) -5(1) + c = 2 + 1  - 5 + c = 3 - 5 + c = c - 2.

We also know from the question provided that f(1) = 0. We can therefore match this condition with the substitution that we have just made which allows us to make the following statement. f(1) = c - 2 = 0.

We can then rearrange this equation in order to get an expression for c by adding 2 to both sides, therefore c = 2.

Answered by Calum L. Maths tutor

3128 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Integrate 1/(1 - 3*x) with respect to x


how can differentiate using the product and chain rule? e.g y=(4x+1)^3(sin2x), find dy/dx.


Two lines have equations r = (1,4,1)+s(-1,2,2) and r = (2,8,2)+t(1,3,5). Show that these lines are skew.


A curve has parametric equations x= 2sin(t) , y= cos(2t) + 2sin(t) for -1/2 π≤t≤ 1/2π , show that dy/dx = - 2sin(t)+ 1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences